PENERAPAN GAMIFIKASI DALAM PEMBELAJARAN NIHONJIJO DI UNIVERSITAS NASIONAL PASIM - Miranti Artarina (Jurnal Sastra - Studi Ilmiah Sastra, 2024)
This study examines the application of gamification in Nihonjijo (knowledge of Japanese culture and society) learning at PASIM National University, particularly for Generation Z students. Despite the increasing global interest in Japanese culture and language, Generation Z exhibits learning characteristics that diverge from traditional educational frameworks. This research employs an in-depth interview method to identify the specific obstacles faced by students in learning Nihonjijo using conventional methods. The main findings indicate that conventional methods, characterized by rote memorization of vocabulary and kanji characters and grammar-focused instruction, fail to engage this generation, which prefers interactive, technology-based, and contextual learning experiences. The application of gamification in Nihonjijo learning is found to enhance student engagement and motivation by integrating game elements such as points, challenges, and rewards. Additionally, the rapid evolution of digital media and its impact on attention spans and learning preferences are explored. This study concludes that to teach Japanese effectively to Generation Z, particularly in Nihonjijo learning, educators must integrate innovative strategies that align with their digital fluency and need for practical application. Recommendations for curriculum development include further incorporation of gamification, multimedia resources, and more interactive learning practices to create a more immersive and engaging learning environment. This study contributes to the broader discourse on educational reform and highlights the need for adaptive teaching methods in the context of cultural and language studies.